Effectiveness of Experiential Learning Approaches (ELA) in enhancing students’ active participation in physical education - Buen, Ralph Julius; Carcahente, Carlito; Chu, Paula Danielle; Limbo-Rivera, Charis (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2024)
Background: Active participation in physical education (PE) is essential for students’ development yet remains challenging in many schools. Research Objectives: This study aimed to assess the effectiveness of experiential learning approaches, including role-playing and interactive simulations, in enhancing students’ willingness and ability to actively participate in PE at Gabas Integrated School (GIS). Methods: This study utilised a one-group pretest-posttest design in which 34 Grade 9 GIS students participated. A researcher-made survey questionnaire patterned from the Students’ Participation Survey and the Motivation in Physical Education Survey and a checklist tool were used to gather data. Education experts reviewed the survey questionnaire to ensure content validity and conducted a pilot test. The collected data were analysed using Jeffrey’s Amazing Statistics Program (JASP). Findings/Results: The study revealed that the students’s willingness to participate was initially moderately willing, which increased to extremely willing after the intervention. The student’s ability to participate improved from a participative rating to a highly participative rating after the intervention. The Wilcoxon signed-rank test further revealed significant differences between the students’ willingness and ability to participate before and after the intervention. Conclusion: These findings concluded that an experiential learning approach effectively enhances students’ active participation in terms of their willingness and ability to participate in PE classes. Thus, the Department of Education must encourage teachers to use ELA to transform students from passive spectators to active participants. Physical education teachers must also consider incorporating performance-based learning and real-life scenarios that allow students to apply their skills in meaningful contexts to their physical education teaching.